«Менеджмент многообразия» в реализации стратегии инновационного развития организаций - Стадник, Валентина Васильевна (International Dialogues on Education Journal, 2017)
The organizational conditions of diversified management implementation have been characterized. The features of heterarchy as an effective form of development of diversity inside organizations have been distinguished. The possibilities of heterarchy in a context of formation of the environment of active innovative search has been shown through decentralization of management and development of organizational interaction. It has been pointed on important role of motivational function in a realization of “diversity management” concept. It has to provide unity of goals of participants of innovative search inside particular enterprise and inside pool of enterprises.